Decentralized energy: How 100% renewable energy regions affect households' energy saving behavior - Alessandro De Palma; Marco Faillo; Roberto Gabriele (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
This paper focuses on decentralized energy in Germany and how households' environmental behavior in terms of energy consumption is shaped in these contexts. It sets out to gain a more precise understanding of whether decentralized energy initiatives are a good tool to promote the adoption of renewable energies and engagement in other sustainable behaviors to mitigate global warming. This study would be one of the first to investigate the effect of living in 100% Renewable Energy Regions, i.e., regions committed to achieving the status of 100% renewable, on households' behavior using a large-scale dataset, with a quasi-experimental setting. The analysis, indeed, combines micro-level data from the German Socio-Economic Panel (SOEP) with information on the Landkreis (districts) that took part in a regional energy project aimed at supporting regions to achieve 100% neutrality of energy production: Project 100% ErneuerbareEnergie-Regionen (100ee-Region). The findings show that German households living in these districts have considerably increased their energy consumption through the years with respect to untreated households. Moreover, results report that the adoption of renewable energies mediates the effect of the treatment on energy usage, outlining a concave parabolic relationship between the mediator and the outcome. These findings, based on real-world evidence, provide powerful information that should be considered by policymakers when promoting the decentralization of energy. Moreover, this study fits into the literature on the determinants of pro-environmental behavior, showing that contextual factors are crucial drivers of it.
Keywords: C22; D19; Q40; Q48; Q28; 330; Decentralized energy; energy behavior; rebound effects; Germany; policy evaluation